2017
DOI: 10.1002/wcms.1321
|View full text |Cite
|
Sign up to set email alerts
|

Theory and applications of surface micro‐kinetics in the rational design of catalysts using density functional theory calculations

Abstract: Rational design of catalysts has long been an important and challenging goal in heterogeneous catalysis. To achieve this target, density functional theory (DFT) calculations and micro‐kinetics are two of the cornerstones. The DFT calculations make it possible to obtain microscopic properties of catalytic systems by computational simulations, and the micro‐kinetic modeling of surface reactions provides a tool to link quantum‐chemical data with macroscopic behaviors of the systems. In this review, we focus on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 93 publications
(220 reference statements)
0
26
0
Order By: Relevance
“…In the last decade, significant advances have been achieved in the atomistic-theoretical calculations, enabling us to computationally construct molecular and crystalline structures and to reveal the reaction pathways on the catalyst surface at atomic-molecular level (Nicholson et al., 2014, Qin et al., 2018, Studt et al., 2014, Mao et al., 2017). Therefore, the RWGS reaction mechanism on InNi 3 C 0.5 is first investigated by the density functional theory (DFT) calculations.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, significant advances have been achieved in the atomistic-theoretical calculations, enabling us to computationally construct molecular and crystalline structures and to reveal the reaction pathways on the catalyst surface at atomic-molecular level (Nicholson et al., 2014, Qin et al., 2018, Studt et al., 2014, Mao et al., 2017). Therefore, the RWGS reaction mechanism on InNi 3 C 0.5 is first investigated by the density functional theory (DFT) calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations and experimental results have indicated that Pd–M alloys will undergo phase segregations upon annealing at elevated temperature, resulting in a pure Pd overlayer on the bulk alloys, where M represents transition metals [ 16 , 17 ]. Using the d -band model proposed by Nǿrskov et al, the enhanced catalytic activity is explained by the electronic and geometric influence of the alloying element, making the overlayer Pd atoms different from Pd atoms in the bulk [ 8 , 18 , 19 , 20 ]. However, the critical problem of this Pd alloy core/shell structure is that the core generally consists of random distributed atoms depending on Pd/M ratios, making it difficult to determine and control the active sites experimentally [ 11 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of catalytic reactions, microkinetic modelling is proposed as a most suitable approach to enhance the understanding and enable the optimisation of plasmaenhanced heterogeneous catalytic reaction systems, based on the demonstrated ability of the method in thermal catalysis of accelerating catalyst and process design via reaction mechanism elucidation and catalyst discrimination. 186 Elaborate microkinetic models have been developed for Figure 15. Arrhenius plot for the forward reaction rate constant.…”
Section: Discussionmentioning
confidence: 99%